Common-mode noise reduction circuit design for biosignal acquisition system-in comparison with the DRL - Chen, Minghui; Wang, Jianqing; Anzai, Daisuke; Fischer, Georg (IEEJ Transactions on Fundamentals and Materials, 2019)
Common-mode (CM) noise is a primary interference to biological signal (biosignal) detection systems, but is hardly solved with passive filtering. Conventionally, a driven-right-leg (DRL) circuit is employed to drive down the CM noise level. In this work, We first clarified how much influence an imbalance in the contact resistance could have for three different kinds of circuits, and then proposed a novel design of imbalance cancellation circuit using the digital potentiometer(digiPOT). Simulation evaluations were performed and the results showed that our circuit design can exceed the DRL by more than 20 dB in reducing the CM noise under the same conditions.
CRIS-Team Scopus Importer:2019-12-17
Keywords: Biosignal acquisition; Biosignal sensing; Common-mode noise; Electromagnetic compatibility; Electromagnetic interference; EMC